2012
DOI: 10.1111/j.1399-6576.2012.02693.x
|View full text |Cite
|
Sign up to set email alerts
|

Intubation of the morbidly obese patient: GlideScope® vs. Fastrach™

Abstract: No significant difference between the two methods was found. The GS and the FT may therefore be considered to be equally good when intubating morbidly obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Bathory (2010) [30] Andersen (2011) [31] Abdelmalak (2011) [32] Ydemann (2012) [33] Marrel (2007) [34] Dhonneur (2009) [35] Summary success rate (tab) 94.4% Study Bathory (2010) [30] Andersen (2011) [31] Abdelmalak (2011) [32] Ydemann (2012) [33] Marrel (2007) [34] Dhonneur (2009)…”
Section: Studymentioning
confidence: 99%
“…Bathory (2010) [30] Andersen (2011) [31] Abdelmalak (2011) [32] Ydemann (2012) [33] Marrel (2007) [34] Dhonneur (2009) [35] Summary success rate (tab) 94.4% Study Bathory (2010) [30] Andersen (2011) [31] Abdelmalak (2011) [32] Ydemann (2012) [33] Marrel (2007) [34] Dhonneur (2009)…”
Section: Studymentioning
confidence: 99%
“…Summarising all patients in these studies, and accepting an additional attempt at videolaryngoscopy as a success, the success rate of videolaryngoscopy in obese patients has a 95% CI of 0.99 – 1.00 (Fig. ) . Specific for obstetric anaesthesia, limited evidence from a series of 180 intubations for emergency or urgent caesarean section shows that the use of videolaryngoscopy ensured successful intubation at the first attempt in all 18 patients in which it was used as the primary device.…”
Section: The Case For Videolaryngoscopes In Obstetric Anaesthesiamentioning
confidence: 99%
“…The differences in the results between the two devices may be due to different shape, structure, and method of intubation. Arslan ZI et al [5] Ydemann M et al [10] compared Glidescope and ILMA (Fastrach) for intubation of patients suffering from morbid obesity and concluded that ILMA group showed that intubation time was 61 s, 84% of participants (n=42) were intubated in the 1st attempt, 5 patients (10%) could not be intubated in the second attempt and no desaturation occurred.…”
Section: Discussionmentioning
confidence: 99%